The Research of Thangka Buddha Gesture Detection Algorithm - Yan, Xu; Lan, Wang Wei (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
This paper describes both the meaning of split Thangka Buddha gesture and steps, then choice the Canny operator method of edge detection on the thangka Buddha's gesture.Through a simple way of human-computer interaction,the Buddha's gesture will be cut off from Thangka Buddha,and then make simulation experiments by software of Matlab.Finally,through analysis and comparison,expounds the advantages and disadvantages of the algorithm.